A Philosopher's Apprentice : In Karl Popper's Workshop. - Agassi, Joseph. (Schriftenreihe zur Philosophie Karl R. Poppers und des Kritischen Rationalismus / Series in the Philosophy of Karl R. Popper and Critical Rationalism, 2008)
Both a Popper biography and an autobiography, Agassi's A Philosopher's Apprentice tells the riveting story of his intellectual formation in 1950s London, a young brilliant philosopher struggling with an intellectual giant - father, mentor, and rival, all at the same time. His subsequent rebellion and declaration of independence leads to a painful break, never to be completely healed. No other writer has Agassi's psychological insight into Popper, and no other book captures like this one the intellectual excitement around the Popper circle in the 1950s and the struggles of the 1960s and 1970s - personal, academic, political, all important philosophically. Agassi's Popper - whether one agrees with it or not - is an enormous contribution to scholarship. This second revised edition includes also Popper's and Agassi's last correspondence and, in a postscript it shows Agassi leafing through Popper's archives, reaching a sort of reconciliation, an appropriate ending to the drama. A must read." - Malachi Hacohen, Duke University.